Combined malonic and methylmalonic aciduria due to ACSF3 mutations: Benign clinical course in an unselected cohort. Issue 1 (11th February 2019) - Levtova, Alina; Waters, Paula J.; Buhas, Daniela; Lévesque, Sébastien; Auray‐Blais, Christiane; Clarke, Joe T.R.; Laframboise, Rachel; Maranda, Bruno; Mitchell, Grant A.; Brunel‐Guitton, Catherine; Braverman, Nancy E.
Abstract: Background: The clinical significance of combined malonic and methylmalonic aciduria due to ACSF3 deficiency (CMAMMA) is controversial. In most publications, affected patients were identified during the investigation of various complaints. Methods: Using a cross‐sectional multicenter retrospective natural history study, we describe the course of all known CMAMMA individuals in the province of Quebec. Results: We identified 25 CMAMMA patients (6 months to 30 years old) with a favorable outcome regardless of treatment. All but one came to clinical attention through the Provincial Neonatal Urine Screening Program (screening on day 21 of life). Median methylmalonic acid (MMA) levels ranged from 107 to 857 mmol/mol creatinine in urine (<10) and from 8 to 42 μmol/L in plasma (<0.4); median urine malonic acid (MA) levels ranged from 9 to 280 mmol/mol creatinine (<5). MMA was consistently higher than MA. These findings are comparable to those previously reported in CMAMMA. Causal ACSF3 mutations were identified in all patients for whom genotyping was performed (76% of cases). The most common ACSF3 mutations in our cohort were c.1075G > A (p.E359K) and c.1672C > T (p.R558W), representing 38.2 and 20.6% of alleles in genotyped families, respectively; we also report several novel mutations. Conclusion: Because our province still performs urine newborn screening, our patient cohort is the only one free of selection bias. Therefore, the favorable clinical course observed suggests that CMAMMA is probably a benign condition, although we cannot exclude the possibility that a small minority of patients may present symptoms attributable to CMAMMA, perhaps as a result of interactions with other genetic or environmental factors.